TRIGGER OF STOCK RETURN RATE IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Dewi, Mertyani Sari; Ferayani, Made Dwi (KEUNIS, 2022)
Return is the goal of investors to invest in the capital market. Investors do various ways in order to get the desired return, by doing their own analysis of the movement of the company's stock performance or by using analytical tools in the form of financial statements. The purpose of this study is to analyze the effect of Return On Assets, Return On Equity, and Price to Book Value on Stock Returns in food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This research was conducted using a quantitative documentation method. This study uses 520 financial statements per quarter from 26 companies for 5 years as a population. By using purposive sampling method, a sample of 240 financial statements per quarter from 12 companies was obtained. The hypothesis testing method uses the F test, t test, and multiple linear regression analysis. The results of the study state that partially ROA, ROE, and PBV have a positive and significant effect on stock returns. And simultaneously ROA, ROE, and PBV have a positive and significant effect on stock returns with a coefficient of determination of 17%.